The Influence of Profitability, Liquidity, and Solvency on Stock Prices in Transportation and Logistics Sector Companies Listed on The Indonesia Stock Exchange Period 2020-2024 - Abelia Fitri Rahman; Mukhzarudfa; Dica Lady Silvera (Greenation International Journal of Economics and Accounting, 2025)
This study examines the influence of profitability, liquidity, and solvency ratios on stock prices of transportation and logistics sector companies listed on the Indonesia Stock Exchange during the 2020-2024 period. The research employs a quantitative approach using secondary data obtained from annual financial statements. Data analysis is conducted through multiple linear regression, supported by classical assumption tests, simultaneous testing (F-test), and partial testing (t-test). The sample consists of 18 companies selected through purposive sampling, resulting in 90 observations over five years. The results indicate that simultaneously, Return On Assets (ROA), Current Ratio (CR), and Debt to Equity Ratio (DER) have a significant effect on stock prices. However, partially, only Current Ratio shows a significant influence on stock prices, while Return On Assets and Debt to Equity Ratio do not demonstrate significant effects. These findings suggest that corporate liquidity is a primary factor considered by investors in evaluating stock prices within the transportation and logistics sector during the study period. The study contributes to signaling theory by demonstrating that liquidity signals are more relevant to investors than profitability and leverage signals in this specific sector and timeframe.